Is measuring social innovation a mission impossible? - Mihci, Hakan (Innovation, 2020)
The main aim of the paper is to question the viability of measuring social innovation with the current state of knowledge on the one hand, and to make suggestions for better measurement of it on the other. To reach this aim, the literature on the traditional measures of technological innovation and the previous attempts of measuring social innovation is surveyed. Despite relatively narrow scope of the literature mainly originated from the very recent and pioneer experiments, one may argue that the first findings do not present a promising picture for future studies. Therefore, existing trials to measure social innovation have to be critically screened to ascertain problematic areas, and hence, to provide plausible solutions. The problems with social innovation metrics are not only limited with obtaining concrete and trustworthy results, but also extended to statistical, methodological and even conceptual spheres.
Keywords: Indicateur; Innovation; Innovation sociale; Innovation technologique; Mesure d'impact; Réservé UdeM